Tectonics of the Pokrovo-Kireevskaya structure of the Near-Azovian area - Shatalov, N.N. (Reports of the National Academy of Sciences of Ukraine, 2015)
The results of investigations of the large structural Pokrovo-Kireevskaya ore knot within the Near-Azovian megablock of the Ukrainian Shield are presented. The features of fault-block tectonics and its influence on forming the ore knot are defined. The Kalmiuska, Gruzsko-Yelanchikskaya, Yuzhno-Donetskaya, and other fault zones of the orthogonal and diagonal systems and their significance in the localization of unique fluorite rare-earth deposit are characterized, by using satellite images and geological-geophysical data. The features of magmatism manifestation are studied.